YIELD LOSSES OF VUB IN 30 IN VARIOUS LAND OF AGROECOSYSTEM IN WEST KALIMANTAN - Jhon David (Agros Journal of Agriculture Science, 2018)
Postharvest handling of rice aims to improve efficiency, reduce the high yield losses and maintain the quality of grain or rice. The magnitude of shrinkage at each stage of the process is quite varied, such as rice varieties, plant conditions and rice maturity, harvesting and harvesting systems, postharvest machine tools, and milling systems. By applying the right postharvest technology to the growing awareness of the importance of avoiding the food crisis, it is possible to reduce the current shrinkage rate. This study aims to determine the level of loss of harvest losses in 3 agro-ecosystems, conducted in four (4) District 12 sub-districts, with replicates of three each location. The lowest shrinkage rate was obtained in tidal agro-ecosystem (1.35%), and highest semi irrigation (2.14%), the lowest shrinkage rate in 1.27% semi-irrigated agro-ecosystem and highest tidal agro-ecosystem 1.86%